Tangible power: Material displacement and spatial demarcation in Aristophanes’ Brids (De Rebus Antiquis, 2021)
An interpretation of Aristophanes’ Birds based on the theoretical approaches of New Materialism allows us to identify the role of numerous significant objects in the practical display of diplomatic encounters and in the consolidation of abstract colonial claims of a polis like Athens through the representation of its physical support. By alerting in general about the goods and their potential in the hands of a protagonist interested in control and possession, the comedy suggests that the visible objects circulating, imagined or built on stage, which are obtained or transferred, kept or destroyed, can help to acknowledge the tangible bases of Athenian imperial power.
Keywords: Aristophanes; Birds; New Materialism; Borders; Objects; International Relations